Statistics of regional differences and the status of budgetary system of the Russian Federation - O. V. Morozov; A. G. Biryukov; M. A. Vasiliev (Статистика и экономика, 2019)
The purpose of the article is to assess the current state and develop measures of state policy to overcome consistently the interregional differences in the level and quality of life of the population based on promoting the independence of regional and local authorities of the Russian Federation. The applied purpose of the work is to determine the optimal values of the distribution of revenues of the consolidated budget of the Russian Federation at the levels of the budget system as a financial condition of the solvency of the subnational authorities. Due to the provisions of the Decree of the President of the Russian Federation from 07.05.2018 No. 204 “On National Goals and Strategic Objectives of the Development of the Russian Federation for the Period up to 2024” the range of issues is of critical importance, as it requires the inclusion of regional and local authorities in the implementation of national projects.Materials and methods. The paper analyzes the changes in the level of interregional differences in the main indicators of socio-economic development of the Russian Federation for 2000, 2005 and 2016–2018. Based on the analysis of interregional differentiation by the own and total revenues of their consolidated budgets, the changes in the level of financial independence of subnational authorities were assessed. As factors, hindering the development of regions with “selfreliance”, the state debt policy, the policy of inter-budget transfers, as well as the structure of income of the three-level budget system of the country are indicated and analyzed. The methodological basis of the study is the work on regional statistics, structural analysis, quantitative modeling. Tabular and graphic methods of visualization of research results, statistical methods of processing of initial data were used. For the solution of research tasks, the standard packages of the applied programs of Microsoft Windows were used.Results. The article shows the excessive centralization at the Federal level of the main decisions that determine the fiscal and debt policy of regional and local authorities, the “explosive” growth in the volume of subnational debt for these years, as well as the “blurring” of inter-budget transfers from the Federal budget to the budgets of the subjects of the Russian Federation. The debt policy of the state and inter-budgetary regulation are estimated as not fully corresponding to the tasks of spatial development of the country. A system solution for optimizing the structure of three-level budget system of the Russian Federation is proposed and a method for determining the optimal values of the distribution of revenues of the consolidated budget of the Russian Federation by levels of the budget system is given.Conclusion. The paper deals with the differentiation of Russian regions in terms of the level and quality of life of the population, analyzes the factors that led to this differentiation. The high heterogeneity of Russia’s spatial development is one of the features of its economy. State fiscal and debt policy, inter-budget transfer policy are the key factors in consistently solving the problems of overcoming interregional differences in the level and quality of life of the population, improving the competitiveness of the country, ensuring sustainable economic growth. Achieving the optimal structure of the budget system (as well as the movement to it) will create conditions not only for the inclusion of subnational authorities in the implementation of national projects, but also for the implementation of the diversity of the potential of its regions – a unique advantage of the Russian Federation.